Функции прецедентных текстов в публицистических материалах - Барбара, Н. В.; Barbara, N. V. (Волин. нац. ун-т ім. Лесі Українки, 2011)
В статье раccматривается использование российской прессой прецедентных текстов как средства презентации украинской ментальности. Представляя реалии современной жизни в Украине, а благодаря им – ментальные установки нации, СМИ широко используют прецедентные тексты как без изменений, так и актуализированные в соответствии с требованиями контекста и авторского видения. Выделено следующие продуктивные способы трансформации: замена компонентов, добавление нового элемента, одновременная замена и добавление нового компонента, контаминация, аллюзия, синтаксическая актуализация, редукция. This article is devoted to using of precedential texts as means of presentation of Ukrainian mentality by Russian-speaking press. Representing the realities of modern life in Ukraine and through them the mental bases of the nation, Mass Media widely use the precedential texts both without changes and actualized according to the requirements of the context and author’s vision. The further productive ways of transformation are stressed: change of components, adding of a new element, simultaneous change and adding of a new component, contamination, allusion, syntactic actualization, reduction.
Функції прецедентних текстів у публіцистичних матеріалах
The Functions of Case-Law Texts in the Journalistic Materials
Keywords: прецедентный текст; российская пресса; ментальность; способы трансформации преце- дентных текстов; ассоциативные связи; precedential text; Russian-speaking press; mentality; ways of transformation of precedential texts; association contacts